2020
DOI: 10.1177/2050640620936383
|View full text |Cite
|
Sign up to set email alerts
|

Moderate endurance and muscle training is beneficial and safe in patients with quiescent or mildly active Crohn’s disease

Abstract: Background and aims Physical activity is beneficial in several chronic disorders including Crohn′s disease, but the preferred type of exercise is unknown. Our study aimed to examine and compare the safety, feasibility and potential beneficial effects of individual moderate endurance and moderate muscle training in patients with Crohn’s disease. Methods Quiescent or mildly active (Crohn’s disease activity index <220) patients with Crohn’s disease were randomly allocated to either a control, endurance, or mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 36 publications
(84 reference statements)
0
43
0
4
Order By: Relevance
“…This result is not only statistically significant, but also clinically important, as an improvement of only two repetitions has shown clinically important on several outcomes in various diagnosis [25,26]. An RCT with 45 Crohn's Disease participants, randomized to control group, moderate endurance, or muscle training, also showed a significant improvement in the lower extremities measured by leg press test (p < 0.04) [27], while we used squats and chair stand. In their pilot study with 9 participants after an extensive small bowel resection, Araújo et al (2008) found a significant increase in MM after a 14 weeks training intervention in patients with IBD [22].…”
Section: Discussionmentioning
confidence: 72%
“…This result is not only statistically significant, but also clinically important, as an improvement of only two repetitions has shown clinically important on several outcomes in various diagnosis [25,26]. An RCT with 45 Crohn's Disease participants, randomized to control group, moderate endurance, or muscle training, also showed a significant improvement in the lower extremities measured by leg press test (p < 0.04) [27], while we used squats and chair stand. In their pilot study with 9 participants after an extensive small bowel resection, Araújo et al (2008) found a significant increase in MM after a 14 weeks training intervention in patients with IBD [22].…”
Section: Discussionmentioning
confidence: 72%
“…Sarcopenia has been considered to be a meaningful marker of an adverse prognosis in patients with CD ( 48 50 ). Recent studies reported that moderate endurance and muscle training were beneficial for patients with quiescent or mildly active CD ( 51 , 52 ), which may imply the potential impact of improved muscle status on disease activity to some extent. This potential effect is somewhat related to the assessment of muscle mass by the GLIM criteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike healthy individuals, there are concerns about exercise intervention for patients with IBD. Although there are a number of studies that demonstrated the safety and efficacy of exercise interventions in patients with IBD, these studies have often been conducted in patients with IBD with mild disease status or in remission, and a thorough evaluation is required to determine whether exercise interventions in patients with active IBD are an aggravating factor for IBD [103][104][105][106][107][108][109]. The significance of exercise intervention for improving sarcopenia in patients with IBD with higher disease activity is unknown [104][105][106][107][108][109].…”
Section: Exercisementioning
confidence: 99%